The Marine Actinobacterium Streptomyces sp. BTA 1-131 as a Potential Producer of Anti-Nontuberculous Mycobacterial (Anti-NTM) - Paramita, Ni Luh Putu Vidya; Atikana, Akhirta; Sukmarini, Linda; Untari, Febriana; Prayoga, Muhammad Bagas; Maulidia, Faiqoh Nur; Ratnakomala, Shanti; Lisdiyanti, Puspita; Nuryastuti, Titik; Hertiani, Triana (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Nontuberculous mycobacteria (NTM) are environmental microorganisms, also known as opportunistic pathogens, found in patients with pulmonary tuberculosis. The emergence of antibiotic resistance is increased by prolonged antibiotic treatment for NTM infections. Therefore, alternative sources of new antibiotics are essential for the treatment of NTM infections. A marine actinobacterium, Streptomyces sp. BTA 1-131, isolated from a marine sponge, Melophlus sarasinorum, has been reported as a potential source of antibacterials and anticancer agents. The present study aimed to investigate the potential of Streptomyces sp. BTA 1-131 against two NTMs: Mycobacterium smegmatis and Mycobacterium fortuitum. Streptomyces sp. BTA 1-131 was fermented in three cultivation media (SYP, ISP2, and YS), and the secondary metabolites were extracted using methanol. The bioactivity screening showed inhibition of all methanolic extracts against the growth of M. smegmatis and M. fortuitum. The methanolic extract, which could inhibit both mycobacteria, was a crude extract derived from SYP liquid medium fermentation. The isolated compounds in this study were preliminarily identified using thin-layer chromatography (TLC). The TLC results showed different potential compounds in the crude extracts of Streptomyces sp. BTA 1-131 also highlighted the impact of the fermentation medium on the production of metabolites from Streptomyces. This study also added knowledge about the importance of the Indonesian marine actinobacterium Streptomyces sp. BTA 1-131 as a promising producer of anti-NTM compounds.